Temporomandibular Joint Gap Arthroplasty in Cats - Aghashani, Armeti; Verstraete, Frank J. M.; Arzi, Boaz (Frontiers in Veterinary Science, 2020)
Abstract Temporomandibular joint (TMJ) ankylosis is defined as fibrous or bony fusion of the mandibular head of the condylar process and the mandibular fossa of the squamous part of the temporal bone. Ankylosis of the TMJ may be intraarticular, extraarticular, or both. The objective of this report is to describe the surgical planning, technique and outcome of gap arthroplasty for extensive TMJ ankylosis in cats. Client-owned cats (n = 7) were examined clinically and surgical planning included the use of cone-beam computed tomography (CBCT) and tridimensional (3D) printed models. In 6 of the 7 cats, temporary tracheostomy intubation was required. Gap arthroplasty included zygomectomy, coronoidectomy, condylectomy, as well as fossectomy (removal of the mandibular fossa of the temporal bone) and was performed using a piezosurgical unit. In all 7 cats, gap arthroplasty was performed without surgical complications. In addition, a clinically acceptable mouth opening was achieved in all cases. However, a noticeable mandibular instability was observed. Medium-term follow-up demonstrated acceptable quality of life with one case of recurrence of ankylosis requiring repeated bilateral surgery, and a second case with recurrence of ankylosis not requiring surgical intervention. We concluded that TMJ gap arthroplasty in cats is a salvage procedure indicated in cases of severe intraarticular and extraarticular ankylosis. Diagnostic imaging by means of CBCT and 3D printing are essential for precise surgical planning. The use of piezosurgical unit allows for safe and precise ostectomy. Clinically, despite the resulting mandibular instability, appropriate prehension of food and water was possible.